Intracerebral recordings of the Bereitschaftspotential demonstrate the heterogeneity of its components - Kukleta, Miloslav; Turak, Baris; Louvel, Jacques (International journal of psychophysiology, 2012)
Though consisting of early and late components, the evoked potential preceding a voluntary movement (Bereitschaftspotential - BP) is often considered as a unitary phenomenon. By analyzing intracerebrally recorded BP we attempted to demonstrate that the components are electrophysiological correlates of separate operations. The BPs recorded in 42 epilepsy surgery candidates (28 men, 14 women; aged from 18 to 49 years) during self-paced clenching movements of the hand opposite to the explored hemisphere were investigated in the study. Microdeep intracerebral 5 to 15-contact electrodes were used. The averaged curves were calculated from approximately 30 trials in each case. All the records were taken with a binaural reference. The total number of explored brain regions was 235; the event-related premovement potentials were observed in 121 of them. Three types of premovement responses were observed: (i) the BP with both components; (ii) the BP with the early component only; and (iii) the BP with the late component only. The generators of the early one-component BP were demonstrated in two frontal cortical areas (precentral and middle frontal gyri) and in the parietal area known to be involved in action planning and decision making (precuneus). Some structures generating the early one-component BP were activated during movement; the others were without motor responsiveness. The results suggest a separate elaboration of functional task items in some and their integration in other brain structures, and the existence of volitional mechanisms of different hierarchical character.
Keywords: Epilepsy; epilepsie; Humans; lidé středního věku; mapování mozku; Decision Making; Hand Strength; Female; Contingent Negative Variation; mladý dospělý; dospělí; rozhodování; lidé; elektroencefalografie; mozková kůra; Electromyography; časové faktory; Cerebral Cortex; Brain Mapping; Adult; síla ruky; pohyb; ženské pohlaví; Male; Middle Aged; Adolescent; Movement; Electroencephalography; Young Adult; mužské pohlaví; Time Factors; elektromyografie; kontingentní negativní variace; mladiství